Factors influencing recurrence after complete remission in children with hepatoblastoma: A 14-year retrospective study in China - Li, Fan; Zhang, Weiling; Hu, Huimin; Zhu, Xia; Zhang, Yi; Huang, Dongsheng (PloS one, 2021)
After a complete remission to treatment for hepatoblastoma, some children still have recurrence. We identified and explored the factors that influence recurrence after complete remission in a retrospective study. Of 197 children with hepatoblastoma, 140 (71.1%) achieved initial complete remission and were enrolled in factor analysis. Variables consisted of age, sex, PRE-Treatment EXTent of tumor (PRETEXT) stage, pathologic type, metastatic disease, serum alpha-fetoprotein level, vascular involvement, and surgical margin status. We employed univariate and multivariate analyses to assess the relationship between each factor and tumor recurrence. Of 140 children who achieved initial complete remission, 42 (30%) had recurrent hepatoblastoma. The 5-year overall survival rates for the non-recurrence and recurrence group were 99.0% and 78.6%, respectively. The overall 1-year, 3-year, and 5-year recurrence-free survival (RFS) rates were 77.8%, 69.8%, and 69.8%, respectively. All recurrences occurred within 2 years from complete remission. The RFS rate was significantly higher in children younger than 3 years and in those with mixed pathological type, PRETEXT II and III, without metastatic disease, without vascular involvement, and microscopic negative margin than in that of children older than 3 years, with epithelial pathological type, PRETEXT IV, metastatic disease, vascular involvement, and macroscopic positive margin (P < 0.001, = 0.020, < 0.001, = 0.004, = 0.002, and < 0.001, respectively). The independent risk factors for recurrence after complete remission were age ≥3 years, PRETEXT IV, and metastatic disease (P < 0.05). Age, PRETEXT stage, metastatic disease, vascular involvement, pathologic type, and surgical margin status might be associated with recurrent hepatoblastoma after complete remission; meanwhile, age ≥3 years, PRETEXT IV, and metastatic disease are independent risk factors of recurrence. Further research is needed on the causes of tumor recurrence, which may improve the long-term outcomes of children with hepatoblastoma.